A computational framework to support probabilistic criticality modelling for the geological disposal of radioactive waste - E. Adam Paxton; Jiejie Wu; Tim Hicks; Slimane Doudou; David Applegate; Robert Mason; Andrew Price; Liam Payne (Annals of Nuclear Energy, 2025)

Effects of site characteristics and stand management on biomass and carbon sequestration in spotted gum (Corymbia citriodora subsp. variegata) plantations - Trinh Huynh; David J. Lee; Tom Lewis; Grahame Applegate (Forest Ecology and Management, 2023)

The role of sand lances ( Ammodytes sp.) in the Northwest Atlantic Ecosystem: A synthesis of current knowledge with implications for conservation and management - Michelle D. Staudinger; Holly Goyert; Justin J. Suca; Kaycee Coleman; Linda Welch; Joel K. Llopiz; David Wiley; Irit Altman; Andew Applegate; Peter Auster; Hannes Baumann; Julia Beaty; et al. (Fish and Fisheries, 2020)
The American sand lance ( Ammodytes americanus , Ammodytidae) and the Northern sand lance ( A. dubius , Ammodytidae) are small forage fishes that play an important functional role in the Northwest Atlantic Ocean (NWA). The NWA is a highly dynamic ecosystem currently facing increased risks from climate change, fishing and energy development. We need a better understanding of the biology, population dynamics and ecosystem role of Ammodytes to inform relevant management, climate adaptation and conservation efforts. To meet this need, we synthesized available data on the (a) life history, behaviour and distribution; (b) trophic ecology; (c) threats and vulnerabilities; and (d) ecosystem services role of Ammodytes in the NWA. Overall, 72 regional predators including 45 species of fishes, two squids, 16 seabirds and nine marine mammals were found to consume Ammodytes . Priority research needs identified during this effort include basic information on the patterns and drivers in abundance and distribution of Ammodytes , improved assessments of reproductive biology schedules and investigations of regional sensitivity and resilience to climate change, fishing and habitat disturbance. Food web studies are also needed to evaluate trophic linkages and to assess the consequences of inconsistent zooplankton prey and predator fields on energy flow within the NWA ecosystem. Synthesis results represent the first comprehensive assessment of Ammodytes in the NWA and are intended to inform new research and support regional ecosystem‐based management approaches.

Relationships among white-tailed deer density, harvest, and landscape metrics in TN, USA - Heidi L. Adams; Robert E. Kissell; Daryl Ratajczak; Edward L. Warr; Roger D. Applegate; Lynn Barrett; Tabitha Lavacot; David Graves (European Journal of Wildlife Research, 2020)
Landscape and harvest indices are frequently used to represent white-tailed deer ( Odocoileus virginianus ) density. However, the relationship between deer density and specific landscape indices is unclear. Harvest is another metric often used to estimate deer density. Our objective was to model the relationship among deer density, landscape metrics, and harvest density of deer in TN, USA. We estimated deer density across 11 regions in 2011 using distance sampling techniques. We developed 18 a priori models to assess relationships among deer density, harvest density, and landscape metrics. Estimates of deer density ranged from 1.85 to 19.99 deer/km 2 . Deer density was best predicted by harvest density and harvest density + percent woody area. However, harvest density was the only important variable in predicting deer density (Σω i = 0.700). Results of this study emphasize the significance of harvest density in deer management. While the importance of harvest as a management tool for deer is likely to increase as landscapes are fragmented and urbanized, specific management guidelines should be based upon deer densities and landscape metrics when they are important.

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Multi-scale groundwater flow modeling during temperate climate conditions for the safety assessment of the proposed high-level nuclear waste repository site at Forsmark, Sweden - Steven Joyce; Lee Hartley; David Applegate; Jaap Hoek; Peter Jackson (Hydrogeology Journal, 2014)